Os impasses do ensino superior privado brasileiro: o professor e a perversão do laço formativo - Isael de Jesus Sena (2020)
This thesis aims to reflect on the deleterious effects produced in the formative bond, in the relationship between the teacher and the student, as a consequence of the privatization of Brazilian university education. In the name of the fight against social inequalities and the massive exclusion of young people from access to higher education, the Brazilian government of then president, Fernando Henrique Cardoso (1995-2003), implemented a set of public policies that enabled the expansion of the elementary, secondary and university education system. In the continuity, the leftwing governments, initially the former president Luíz Inácio Lula da Silva (2003- 2011) and after the former president Dilma Vana Roussef (2011-2016), interestingly, contributed to this same process, maintaining a focus on the privatization policy, by fostering the opening of new higher education institutions, deserving of indirect financial subsidies from the national state. This privatization process has been reduced to a commodification of higher education and, therefore, contrary to what has been proclaimed, it was accompanied by a quality pauperization of the academic-professional formation, which translates, among other things, into undervalued diplomas in the labor market. In order to produce a displacement in this socioeconomic debate, thanks to psychoanalytic conceptual tools, we point to the deleterious subjective effects on teachers and university students. The mercantilization of university education by the “Brazilian way” ends up producing a perverse or cynical twist in the subjective bond between teacher and student that, by making its genuine development impossible, may be inducing them to a picture of apathy or generalized formative melancholy. Therefore, the intended fight against social inequalities ends up falling with usury in what it says to combat.